PROCESSING OF BOAR’S SPERMIN ARTIFICIAL INSEMINATION CENTRE AT BATURITI - M. P. F., Stradivari; Sumardani, N. L. G.; Mariani, N. P. (Jurnal Peternakan Tropika; Vol 7 No 1 (2019): Vol. 7 Isssues 1 (2019); January - April 2019, 2019)
This study aims to determine the parameters the process of boar’s sperm in the Bali Provinci Artificial Insemination Center. Data collected obtained by survey techniques, interviews and direct observation. As wfell as data retrieval based on records of the results of boar’s sperm shelter during the month of October 2018 in the Artificial Insemination Center Baturiti. The variables observed in Student Work Practices include: processing boar’s spermin the Artificial Insemination CenterBaturiti, Tabanan. Based on the results of Student Internship, it can be concluded that in general the processing of semen at the Bali Provinci Artificial Insemination Centerincludes the process ofsemen storage, semen dilution process, cement storage and the amount of liquid cement production in accordance with the target. Key word: processing of boar’s semen, boar’s semen